Innovative technologies of sports selection and orientation as the basis of elite sport - Popovich, A. P.; Gordievskaya, V. I.; Kolomiychuk, T. A.; Shchepanova, A. V.; Kuptsova, A. N. (The Russian Journal of Physical Education and Sport, 2019)
The level of achievements in modern sport is extremely high. In order to be successful at sports arena it is necessary to have specific morphological features and unique abilities. Selection and orientation form the structure of a long-term training in sport. During selection and ori-entation, complex observations and program research works are held in order to gather full information about the athlete: his health state, anthropometric data, morphological-functional pecu-liarities, central nervous system (CNS) peculiarities, and ability to learn and master motor technical-tactical activity, adaptability to the loads. Mastering the process and technology of selec-tion, diagnostics, estimation and prediction, we can make the conclusion about the future success of the athlete in this or that kind of sport. Research methods. Information sources analysis and summarizing, methods of mathematical statistics. Results. We show the importance of heredity, morphological, physiological and psychological factors during sports selection and in training process. Different authors describe the stages of sports selection. Complex observations, testing help to gather information about an athlete: his health state, anthropometric data, morphological-functional peculiarities, central nervous system (CNS) peculiarities, ability to learn and master motor technical-tactical activity, adaptability to the loads. Information about the athlete`s consti-tutional-morphological features is necessary in order to determine his propensity for this or that sports activity. Conclusion. Higher educational establishments, which specialize in teaching training staff, should take into account the demands of a modern sport and make curriculum in accordance with the federal state educational standards (FSES). They are directed not only to-ward physical culture and sport theory and methodology but also fundamental disciplines (Physiology, Genetics, Morphology, Medicine and others) study. The specialists, who have this knowledge, are highly demanded not only in elite sport, but also in work with the athletes-beginners.